Infliximab plus azathioprine is more effective than azathioprine alone in achieving mucosal healing in pediatric patients with Crohn's disease. Issue 12 (2nd December 2020) - Melek, Jan; Štanclová, Markéta; Dědek, Petr; Malý, Jan; Bayer, Milan; Pozler, Oldřich; Bureš, Jan
Abstract : Objectives: Over the past few years, mucosal healing (MH) has emerged as a promising goal in the treatment of pediatric patients with Crohnʼs disease (CD). We aimed to assess whether combination therapy with infliximab (IFX) + azathioprine (AZA) was more effective than AZA therapy alone in achieving mucosal healing in pediatric patients with CD. Methods: Newly diagnosed pediatric patients with CD at the Department of Pediatrics in University Hospital in Hradec Králové were retrospectively recruited (2000‐2014). The patients were divided into two groups according to the therapy: (a) IFX + AZA ± corticosteroids ± 5‐aminosalicylic acid (5‐ASA) (n = 16); and (b) AZA ± corticosteroids ± 5‐ASA (n = 40). The patients were also divided into two groups: "MH" and "no MH, " according to their MH status. MH was defined as the complete endoscopic disappearance of all mucosal ulcerations (including aphthous ulcerations) and the absence of any sign of mucosal inflammation in the terminal ileum and the large bowel. Results: Of 56 patients, MH was observed in 56% (9/16) treated with combined therapy in comparison with 15% (6/40) of patients in the AZA group ( P = 0.006). The median dose of AZA in both groups was 2.1 mg/kg per day. We observed eight adverse events in seven patients from the IFX + AZA group. Adverse effects were less common in the AZA group ( P = 0.002). Conclusion: Combined therapy (IFX + AZA) was more effective in achieving MH in pediatric CD than treatment with AZA alone.